Analysis of the plastic flow problem for hardening materials under plane strain conditions - PIWNIK, M. (Engineering Transactions, 1990)
Plastic yielding problem is considered in the case of material obeying the kinematic and isotropic hardening rules, rotations of the principal stress directions (PSD) being taken into account. The solution is obtained by means of the slip-line theory under plane strain conditions. Plastic nonhomogeneity and anisotropy are described by the Huber-Mises condition and the hardening rules. An example is given, concerning the problem of bending of a strip weakened by two semi-circular notches; the result is compared with the case of rigid-perfectly plastic material.